A Study On The Adoption Of Intelligent Tutoring Systems (ITS) Readiness On UAE Higher Education Institutions - Alshmsi, Mohammed Saeed Salem Alwami; Hamid, Nor Aziati Abdul (Tropical Scientific Journal, 2025)
Objective: Intelligent Tutoring Systems (ITS) in higher education utilize artificial intelligence to provide personalized learning experiences, effectively replicating one-on-one tutoring by adapting content and feedback to individual student needs. Despite advancements in educational technology, the adoption of ITS in UAE higher education institutions remains limited due to various cultural, social, and educational challenges. This study aims to assess the readiness for ITS adoption in UAE higher education institutions. Research Method: A quantitative research approach was employed, utilizing a structured questionnaire survey administered to 234 participants. Descriptive analysis was conducted to rank key factors influencing ITS adoption readiness, while correlation analysis examined relationships between these factors and performance indicators. Findings: The findings highlight critical determinants of ITS adoption readiness, revealing both strong support and existing concerns within the UAE higher education context. Correlation analysis indicates that ITS adoption readiness is positively influenced by factors such as Performance Expectancy, Effort Expectancy, Social Influence, Facilitating Conditions, Innovativeness, and Optimism. These factors exhibit strong correlations with key performance indicators, including Performance Enhancement, Administrative Efficiency, and Personalized Learning, suggesting a generally high level of preparedness for ITS adoption. However, moderate correlations with factors like Discomfort and Insecurity underscore the need to address potential concerns regarding implementation challenges and perceived risks. Originality: This study provides valuable insights for policymakers and educational institutions seeking to enhance ITS adoption and integration in UAE higher education.